Generation and removal of apparent singularities in linear ordinary differential equations with polynomial coefficients; Theoretical and Mathematical Physics; Vol. 189, iss. 3 - Slavyanov S. Yu.; Satco D. A.; Ishkhanyan A. Artur; Rotinyan T. A. (2016, 2016)
Title screen